ANALISIS PENGELOMPOKAN BANK UMUM KONVENSIONAL DI INDONESIA DENGAN METODE K-MEANS CLUSTERING - I NYOMAN ARIANA GUNA (GANEC SWARA, 2023)
The purpose of this study is to determine the grouping of conventional commercial banks in Indonesia which include healthy, unhealthy and unhealthy bank clusters. Data analysis was performed using the K-Means Clustering methodBased on the data analysis, the results are (1) there are three conventional commercial banks which are categorized as healthy bank groups or clusters, namely: Bank Rakyat Indonesia, Bank Mandiri and Bank Central Asia; (2) there are nine conventional commercial banks that fall into the category of unhealthy bank groups or clusters, namely: West Java and Banten Banks, BTPN Bank, CIMB Niaga Bank, Danamon Bank, DBS Indonesia Bank, Maybank Indonesia Bank, OCBC NISP Bank, Panin Bank and Permata Bank; (3) there are 32 conventional commercial banks which are categorized as unhealthy bank groups or clusters, namely: Bali BPD Bank, Yogyakarta Special Region BPD Bank, DKI Bank, Central Java Bank, East Java Bank, West Kalimantan Bank, East Kalimantan Bank, Lampung Bank , West Sumatra Bank, Papua Bank, South Sulawesi and West Sulawesi Bank, North Sulawesi Bank, North Sumatra Bank, ANZ Indonesia Bank, Bumi Arta Bank, Capital Indonesia Bank, CCB Indonesia Bank, Commonwealth Bank, CTBC Bank Indonesia, Ganesha Bank, Bank HSBC Indonesia, Bank ICBC Indonesia, Bank Ina Perdana, Bank KB Bukopin, Bank KEB Hana Indonesia, Bank Mega, Bank Multiarta Sentosa, Bank Resona Perdania, Bank of America, Bank of China, Citibank and Standard Chartered.